2018
DOI: 10.4012/dmj.2016-407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resin-based and glass ionomer sealants with regard to fluoride-release and anti-demineralization efficacy on adjacent unsealed enamel

Abstract: This study compared resin-based and glass ionomer sealants with regard to their fluoride-release behavior and anti-demineralization potential on adjacent unsealed enamel surfaces. Sealant cavities prepared on bovine enamel blocks were filled with fluoride-containing resin sealants [TeethmateF-1 (TF), Clinpro TM (CP)], and glass ionomer sealant [Fuji VII (FVII)]. Specimens were then incubated in artificial saliva for 14 days to measure fluoride. Thereafter, demineralization was performed for 10 days, and the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
2
15
0
2
Order By: Relevance
“…22 This remaining material modifies the anatomy of the fissures and facilitates the removal of dental plaque by tooth brushing from fissures that otherwise would be inaccessible 22 , it also promotes some release of fluoride to the adjacent enamel. 41,42 Both processes seem to explain the lack of caries progression even after total or partial loss of the sealant.…”
Section: Discussionmentioning
confidence: 99%
“…22 This remaining material modifies the anatomy of the fissures and facilitates the removal of dental plaque by tooth brushing from fissures that otherwise would be inaccessible 22 , it also promotes some release of fluoride to the adjacent enamel. 41,42 Both processes seem to explain the lack of caries progression even after total or partial loss of the sealant.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies showed a moderate risk of bias overall (Table 1). Only six studies out of the thirty-nine included studies were judged to have a low risk of bias [27][28][29][30][31][32] (Table 2). Randomization and blinding were not reported in most of the included studies, leading to a positive risk of bias (Figure 2).…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
“…In general, the sample type was varied between the use of human non-carious teeth or samples made from the tested materials. Generally, most of the studied materials were light-cured, except for a few studies which used chemically cured materials [18,28,39,42,56,58,60]. The remineralizing agents in the tested materials included F, amorphous calcium phosphate (ACP), bioactive glass, strontium (Sr), hydroxyapatite (HAP), calcium silicate (CS), boron nitride nanotubes (BNNT), and calcium phosphate (CaP).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(9,15) The remnants render the pit and fissures to be of less than normal depth, thus permitting better plaque control and prevention of demineralization. (12) Invitro studies (15,16) have revealed initial release of large amount of fluoride from the glassionomer cement (burst effect). The fluoride release continues over the next few weeks, possibly due to slow dissolution of the glass particles into acidified water of the hydrogel matrix.…”
Section: Introductionmentioning
confidence: 99%